INVESTIGATION OF NANO-SILVER PARTICLES ADDITION IN THE OIL EXTRACTED FROM TWO TYPES OF ALMOND (AMYGDALUS SCOPARIA, AND AMYGDALUS LYCIOIDES) AND ITS EFFECT ON THE FATTY ACID PROFILES - Amir Peikar, Rezvan Mousavi Nadoushan, Mohammad Rabbani, Farzad Karimpour (International Journal of Modern Agriculture, 2021)
Almond oil showed significantly higher unsaturated fatty acids compare to saturated fatty acids. They could be used in cosmetic products and human nutrition. In this work, amygdalus scoparia (A.Sc) and amygdalus lycioides (A.Ly) were utilized as the raw material for oil extraction. The Scanning Electron Microscope (SEM) assessed the efficiency of the oil extraction process. Since the evaluation of changes in fatty acids profile is of great importance in nutritional value of oils, researchers decided to evaluate their changes in presence of nano silver particles. Several methods have been proposed to extract oil from plants and oil seeds. In this study, the oil of two types of almonds, A.SC and A.LY, was extracted using Soxhlet extractor with hexane solvent. The amount of fatty acids profile in these types of oil was investigated employing Gas Chromatography (GC-FID). Adding different ratios of nano-silver particles to the oil, the effect of these adding particles on the fatty acids profile was evaluated. In each analysis of both almond oils, the amount of saturated fatty acids (SFA), total unsaturated fatty acids (TUFA), and iodine value (IV) were calculated. The experimental results confirmed that the overall increase in nano-silver particles has approximately increased TUFA. Moreover, the results also revealed that the highest amount of TUFA / SFA in each type of almond oil is associated with the use of 0.04 g nano silver powder in the oil samples. The obtained results could be utilized in scientific and food industry studies, particularly in examining the impact of heavy metals, such as silver effect on the oil industry. Since oleic and linoleic acid are essential for human body, it could be argued that these almond oil has a high nutritional value.